The effect of genotype, lactation and season on the periparturient rise in faecal egg counts in Ethiopian highland ewes: preliminary observations - Tembely, S.; Lahlou-Kassi, A.; Rege, J.E.O.; Mukasa-Mugerwa, E.; Anindo, D.O.; Baker, R.L. (International Foundation for Science, 1996)
The effect of genotype, lactation and season on the periparturient rise in faecal egg counts in Ethiopian highland ewes: preliminary observations. A study was carried out at the International Livestock Research Institute (ILRI) Debre Berhan Research Station Between May 1992 and January 1995 to compare the periparturient rise in faecal nematode egg counts (FEC), packed cell volume (PCV) and body weight (BW) changes in ewes of 2 indigenous sheep breeds. A total of 1840 Menz and Horro ewes were mated to 60 rams of their respective breeds following oestrus synchronization to lamb in wet and dry season. A group of 240 ewes was left unmated to serve as controls. Ewes were grazed out on naturally-contaminated pasture. Levels of faecal egg output were monitored at mating, 3 months after mating, 2 weeks before lambing, 2-4 weeks after lambing, 8 and 12 weeks post-lambing. Consistently higher egg counts were observed in pregnant/lactating ewes in both Menz and Horro sheep than their unmated counterparts. A significant (P<0.05) periparturient rise (PPR) occurred 2 weeks before lambing and peaked 2-4 weeks post-parturition for ewes lambing at the end of the wet season (October/November). There was no PPR when lambing occurred at the end of the dry season (June/July). The rise in faecal egg counts (FEC) was associated with both lactation and seasonal availability of third-stage infective larvae on pasture. There were significant (P<0.05) breed differences in long-transformed FEC, PCV values and BW changes. Faecal culture from both breeds confirmed the presence of Ostertagia spp., Trichostrongylus spp., Haemonchus contortus and Dictyocaulus filaria. The role of periparturient rise in FEC in ewes in gastrointestinal nematode transmission is discussed.